ANALISIS SELF-CONFIDENCE MELALUI TARIAN TEA EKU DENGAN MENGGUNAKAN PBL PADA SISWA SMP MATERI BANGUN DATAR - Sofia Sa'o; Maria Fatima Mei; Agustina Mei; Bertinsia Eku (Program Studi Pendidikan Matematika, 2023)
This study aims to analyze self-confidence from learning outcomes through the tea-eku dance using problem-based learning in junior high school students. The sample in this study was 15 people in class VII Adhyaksa Middle School. The instrument used is a self-confidence questionnaire. namely, a questionnaire composed of 30 items based on indicators: (a) belief in one's abilities; (b) acting independently in making decisions; (c) having a positive self-concept; (d) daring to express opinions; (e) firmness; (f) be responsible. The results showed that of the 15 students, there were 20% or 3 respondents showed high self-confidence, 73%, or 11 respondents showed moderate self-confidence, and 7%, or 1 respondent.